2017
DOI: 10.7150/jca.17394
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200a inhibits cell growth and metastasis by targeting Foxa2 in hepatocellular carcinoma

Abstract: Background: MicroRNAs (miRNAs) are a class of endogenous, small non-coding RNAs which function as essential posttranscriptional modulators of gene expression tightly involved in a wide range of diseases, including the hepatocellular carcinoma (HCC). Here, the present study was designed to investigate the expression levels and cellular roles of miR-200a in HCC.Methods: Quantitative reverse-transcription polymerase chain reaction (qRT-PCR) was used to detect the expression levels of miR-200a in serums and cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…miR-199a/b-3p has been found to target the HCC tumor-promoting PAK4 by repression of PAK4/Raf/MEK/ERK pathway both in vitro and in vivo, suggesting that miR-199a/b-3p could be a potential therapeutic option for HCC [47]. Chen et al reported that the decreased miR-200a expression in HCC could lead to abnormal cell growth, migration and invasion via the regulation of its target, transcription factor forkhead box A2 (Foxa2) [48]. Furthermore, lower miR-200a expression also enhanced the side population (SP) of HCC tumors to metastasize via transactivation of ZEB2 expression and the subsequent epithelial-mesenchymal-transition (EMT) activation in HCC tumor cells [49].…”
Section: Ncrnas and Hccmentioning
confidence: 99%
“…miR-199a/b-3p has been found to target the HCC tumor-promoting PAK4 by repression of PAK4/Raf/MEK/ERK pathway both in vitro and in vivo, suggesting that miR-199a/b-3p could be a potential therapeutic option for HCC [47]. Chen et al reported that the decreased miR-200a expression in HCC could lead to abnormal cell growth, migration and invasion via the regulation of its target, transcription factor forkhead box A2 (Foxa2) [48]. Furthermore, lower miR-200a expression also enhanced the side population (SP) of HCC tumors to metastasize via transactivation of ZEB2 expression and the subsequent epithelial-mesenchymal-transition (EMT) activation in HCC tumor cells [49].…”
Section: Ncrnas and Hccmentioning
confidence: 99%
“…Many researchers have reported that miR-200a inhibited HCC cell proliferation,27282930 and that it plays an important role in protecting cardiomyocyte survival under hypoxic conditions. Li, et al31 pointed that miR-200a level was decreased in H/R-cardiac microvascular endothelial cells (CMECs), and thymosin beta 4 attenuated hypoxia-reoxygenation induced CMECs injury by miR-200a-Nrf2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, growing evidence has exhibited that microRNAs can act as prognostic biomarkers for hepatocarcinoma [56,, and Hepatocellular Carcinoma -Advances in Diagnosis and Treatment via the following pathways: (1) promoting cancerous growth and proliferation [77,78,80,83,89,98,99,[102][103][104][105][106][107][108][109][110][111][112][113], (2) inhibiting cancerous apoptosis [77, 78, 86, 99, 101, 107-109, 111, 112, 114], (3) increasing microvessel density in the tumor tissues [77,115], (4) affecting cell cycles [24,25,27,28,[116][117][118][119], (5) increasing the risk of tumor metastasis [77,115], and (6) decreasing the sensitivity of cancer cells to anticancer drugs [115]. For example, Lu et al [115] investigated the prognostic potential of microRNA-1268a for hepatocarcinoma in 411 patients with hepatocarcinoma.…”
Section: Prognostic Potential Of Microrna For Hepatocarcinomamentioning
confidence: 99%